Determinants of domestic and cross-border bank acquisitions in the European Union - Hernando, Ignacio; Nieto, María J.; Wall, Larry D. (Journal of Banking & Finance, 2009)
This paper analyzes the determinants of bank acquisitions both within and across countries in the EU-25 over the period 1997–2004. Our results suggest poorly managed banks (high cost to income) and larger banks are more likely to be acquired by other banks in the same country. The probability of being a target in a cross-border deal is larger for banks that are quoted in the stock market. Finally, banks operating in more concentrated markets are less likely to be acquired by other banks in the same country but are more likely to be acquired by banks in other EU-25 countries.